Kesesuaian Lahan Komoditas Pertanian dan Perencanaan Penggunaan Lahan Berbasis Geospasial di Kabupaten Malaka, Nusa Tenggara Timur - Nahak, Senon Apriyanto; Lanya, Indayati; Trigunasih, Ni Made (Agrotrop : Journal on Agriculture Science, 2024)
Agricultural Commodity Land Suitability and Geospatial-Based Land Use Planning in Malaka District, East Nusa Tenggara. Data and information on land suitability classes for various plant commodities must be available in Malaka District on a geospatial basis so that they are easily accessible. The technology used is a geographic information system (GIS). The aims of this study were to: (1) obtain land characteristics for land suitability classes, (2) map actual and potential land suitability classes, (3) land use plans based on land suitability, (4) provide a land suitability information system. This research was conducted in two sub-districts in Malaka Regency, East Nusa Tenggara. The analysis carried out in this study included: physiographical analysis, field surveys, soil analysis in the laboratory, land suitability analysis, making land suitability maps and land use planning maps, building a geospatial-based land suitability information system. The actual land suitability class for food crops, horticulture and plantations is classified as marginal suitable (S3wa1wa2wa3rc3na1na2na3eh1eh2Ip1) to unsuitable (Nwa2xc) limiting rainfall, dry months, humidity, effective depth, N-total, P2O5, K2O, salinity, slope, erosion hazard and rocks surface. Improvement efforts include tillage, fertilizing urea, phonska, KCl, making drainage channels, setting planting times, making ponds and making bench terraces. Potential land suitability classes are very suitable (S1), moderately suitable (S2wa1wa2rc3xceh1eh2Ip1) to marginally suitable (S3wa2) limiting rainfall, dry months, effective depth, salinity, slope, erosion hazard and surface rocks. West Malaka and Central Malaka Districts first priority in flat areas to develop corn, cassava, cashew nuts, green beans, shallots, tomatoes and watermelons as an alternative. Whereas in the Central Malaka District, the hilly relief is more suitable for coconut, cocoa and cashew plantations and the karst hill relief is an alternative for the development of corn, cassava, green beans, shallots, tomatoes and watermelons.